Trachyonychia in Children: A Comprehensive Review with Recent Updates - Swetalina Pradhan; Debopriya Paul; Rashid Shahid (Wolters Kluwer Medknow Publications, 2024)
Trachyonychia also known as 20-nail dystrophy presents as roughness of nail plate associated with longitudinal ridging giving a sandpaper-like appearance. It has two subtypes: opaque variety and shiny variety. It commonly presents in the pediatric age group 3-12 years but can present at any age. It can be idiopathic or associated with cutaneous or systemic conditions. Alopecia areata, atopic dermatitis, vitiligo, and lichen planus are some of the commonly associated conditions. Diagnosis is clinical and in doubtful cases, biopsy has a role. Onychoscopy as a novel diagnostic modality can be used. Spontaneous resolution is seen in the majority of pediatric patients, so counseling, reassurance, and active nonintervention can be tried. Treatment is mainly for cosmetic concerns or when associated with some systemic conditions. Various treatment modalities are available with variable efficacy. Topical treatment options include tazarotene, topical steroid, and calcipotriol/betamethasone combination, whereas systemic agents such as oral mini-pulse steroid, methotrexate, cyclosporine, and low-dose acitretin have shown beneficial role. Novel treatment modalities such as the use of tofacitinib, fluocinonide 0.05% with bifonazole 1% cream, combination of fractional CO2 laser with topical therapy, and alitretinoin have shown promising results.